Isolation and characterization of Stenotrophomonas rhizophila T3E: a multifunctional rhizobacterium enhancing tomato growth and soil health - Zhang, Xiancui; Liao, Haoran; Cai, Peiwen; Cai, Tong; Si, Hongkai; Yuan, Jinfeng; Yu, Yanan; Zhao, Mingxing; Li, Peng; Zhang, Xianduo; Jiang, Lu; Yang, Liang; et al. (Frontiers in Plant Science, 2025)
IntroductionPlant growth-promoting rhizobacteria (PGPR) serve as sustainable alternatives to chemical fertilizers and pesticides for improving crop productivity. Among them, Stenotrophomonas rhizophila has demonstrated considerable potential to enhance plant growth, yet the mechanisms underlying its effects on plant development and soil health remain insufficiently elucidated.MethodsIn this study, S. rhizophila strain T3E was isolated and identified from the tomato (Solanum lycopersicum) rhizosphere based on morphological and phylogenetic analyses. The growth-promoting traits of T3E were comprehensively characterized through germination and pot experiments, integrated with phytohormone profiling, gene expression and biochemical analyses, soil assessment, and whole-genome sequencing.ResultsInoculation with T3E significantly enhanced radicle length, primary root length, plant height, and seedling fresh weight, while quantitative assays revealed increased levels of indole-3-acetic acid (IAA) and abscisic acid (ABA) in the roots. qRT-PCR analysis showed that T3E upregulated multiple root growth-related genes (e.g., EAT2, LAX2, GTS1, GRFs) and T3E colonization-related genes (pyrB, flmH, pilR, bopD), supporting its strong root colonization ability. Physiologically, T3E treatment enhanced SOD activity, increased glycine betaine and soluble sugar levels, and reduced MDA content, suggesting improved root health and stress resistance. Whole-genome sequencing revealed a 4.31 Mb circular chromosome with 3,744 coding sequences, diverse secondary metabolite biosynthetic gene clusters, and abundant carbohydrate-active enzyme (CAZyme) genes. Soil assays demonstrated that T3E inoculation improved key physicochemical properties (TN, TP, TK, AK) and significantly enhanced the activities of soil enzymes, such as phosphatase, CAT, urease, and sucrase.DiscussionThese findings identify S. rhizophila T3E as a promising multifunctional PGPR that promotes plant growth, strengthens rhizosphere colonization, and enhances soil fertility. This study provides a solid theoretical basis for developing microbial biofertilizers and advancing sustainable agricultural practices.